3A.003 Road traffic and drowning mortality in an African country: a 30-year period. (14th March 2021) - Abio, Anne; Bovet, Pascal; Didon, Joachim; Bärnighausen, Till; Shaikh, Masood Ali; Posti, Jussi P; Wilson, Michael Lowery
Abstract : Background: Road traffic crashes and drowning are among the leading causes of injury mortality among youth, especially in low- and middle-income countries. The aim of this population-based study was to examine trends in road traffic and drowning related mortality from 1989 to 2018 in Seychelles. Methodology: The population civil death register was used to identify cases. Coding was done according to the ICD-10 codes for external causes of mortality. Mortality rates were estimated using the crude and age standardised rates. The WHO standard population was used to standardise the rates. Negative binomial regression was used to estimate the trends and annual percent changes over time. Results: Drowning and road traffic injuries accounted for approximately 21.9% and 17.5% of all injury-related deaths. Males had a higher risk both for drowning (RR 6.14, 95% CI 3.92, 9.62; p<0.001) and road traffic injury mortality (RR 2.25, 95% CI 1.43, 3.53; p<0.001). The drowning age standardised mortality rate was 25.9 per 100000 person-years, and road traffic mortality was 18.0 per 100000 person-years among males; and correspondingly 3.4 per 100000 and 4.6 per 100000 person-years among females, respectively. The drowning mortality increased by less than 0.01%, while the road traffic mortality increased by 2.7% among males. Conclusion: The major cause of mortality was drowning. However, the annual increase in the road traffic mortality was higher during the 30-year period. Learning outcome: Policies to reduce the road traffic crashes need to be actively implemented to reduce related mortality in order to achieve the SDG target.